2011
DOI: 10.1124/dmd.111.042275
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Quantification and Differential Expression of Drug Transporters, Cytochrome P450 Enzymes, and UDP-Glucuronosyltransferases in Cultured Primary Human Hepatocytes

Abstract: ABSTRACT:The levels of metabolizing enzymes and transporters expressed in hepatocytes are decisive factors for hepatobiliary disposition of most drugs. Induction via nuclear receptor activation can significantly alter those levels, with the coregulation of multiple enzymes and transporters occurring to different extents. Here, we report the use of a targeted liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) method for concurrent quantification of multiple cytochrome P450 (P450), UDP-glucuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 28 publications
(38 reference statements)
6
90
2
Order By: Relevance
“…A quantity amounting to 400 ng total RNA per sample was reverse transcribed for first-strand cDNA synthesis following the protocol for High Capacity cDNA RT Kit (Applied Biosystems, Foster City, CA). Relative mRNA expression of main P450s were analyzed by quantitative real-time PCR, as published previously (Schaefer et al, 2012), using custom-made primers (Biomers GmbH, Ulm, Germany) and inventoried TaqMan gene expression assays (Life Technologies/AB).…”
Section: Methodsmentioning
confidence: 99%
“…A quantity amounting to 400 ng total RNA per sample was reverse transcribed for first-strand cDNA synthesis following the protocol for High Capacity cDNA RT Kit (Applied Biosystems, Foster City, CA). Relative mRNA expression of main P450s were analyzed by quantitative real-time PCR, as published previously (Schaefer et al, 2012), using custom-made primers (Biomers GmbH, Ulm, Germany) and inventoried TaqMan gene expression assays (Life Technologies/AB).…”
Section: Methodsmentioning
confidence: 99%
“…We (Deo et al, 2012;Prasad et al, 2013) and others Bi et al, 2012;Kimoto et al, 2012;Ohtsuki et al, 2012;Schaefer et al, 2012;Tucker et al, 2012) have reported data on the expression of some of these hepatic transporters. Here we extended these studies to determine 1) the interindividual variability in expression of OATP1B1 (SLCO1B1), OATP1B3 (SLCO1B3), OATP2B1 (SLCO2B1), and P-gp (ABCB1) in a large set (n = 64) of human liver samples; and 2) the influence of genotype, age, and sex on such expression.…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, the effects of these changes may have minimal overall impact on RSV CL Bile . Available data suggest that expression of MRP3 and MRP4 in rat and human SCH may be relatively stable over days in culture (Swift et al, 2010a;Ohtsuki et al, 2012;Schaefer et al, 2012). However, robust quantitative proteomics data for transport proteins that mediate CL BL are not yet available.…”
Section: Hepatic Basolateral Efflux Of Rosuvastatinmentioning
confidence: 99%